Multi-Objective Vendor Selection Problem of Supply Chain Management Under Fuzzy Environment - Gupta, Srikant; Ali, Irfan; Ahmed, Aquil (Journal of the Operations Research Society of China (Internet), 2021)
Survival of a company in today’s competitive business environment depends mainly on its supply chain. An adequate supply chain gives a competitive edge to a company. Sourcing, which is the initial stage of a supply chain, can be made efficient by making an appropriate selection of vendors. Appropriate vendor selection results not only in reduced purchasing costs, decreased production lead time, increased customer satisfaction but also in improved corporate competitiveness. In general, the vendor selection problem is a multi-objective decision-making problem that involves some quantitative and qualitative factors. So, we have considered a multi-objective vendor selection problem (MOVSP) with three multiple objective goals: minimization of net ordering price, minimization of rejected units and minimization of late delivered units. In most of the cases, information about the price of a unit, percentage of rejected units, percentage of late delivered units, vendor rating value and vendor quota flexibility may not be known precisely due to some reasons. In this paper, imprecision in input information is handled by the concept of a simulation technique, where the parameter follows the uniform distribution. Deterministic, stochastic, α -cut and ranking function approaches are used to get the crisp value of the simulated data sets. The four different algorithms, namely—fuzzy programming, goal programming, lexicographic goal programming and D 1 -distance algorithm, have been used for solving the MOVSP. In last, three different types of simulated data sets have been used to illustrate the work.